PENGARUH KUALITAS PEMBELAJARAN TERHADAP PRESTASI SISWA PADA BIDANG STUDY PENDIDIKAN AGAMA ISLAM DI MA ROUDLOTUS SHOLIHIN KECAMATAN AIR HITAM KABUPATEN LAMPUNG BARAT - Ahmad Abdurrahman (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
Abstract Students' learning achievement is greatly influenced by the teacher's teaching motivation at school. To improve learning achievement, teachers must be able to develop motivation in every teaching and learning activity. Therefore, there needs to be a communicative learning and teaching atmosphere between teachers and students, because it can stimulate students' learning motivation to carry out learning activities effectively and efficiently.The research problems in this study are:How is the teacher's teaching motivation at SMA Mardi Utomo Tarokan Kediri?How is the students' learning achievement in Islamic Education at SMA Mardi Utomo Tarokan Kediri?Is there an influence of teacher's teaching motivation on students' learning achievement in Islamic Education at SMA Mardi Utomo Tarokan Kediri?This research is a quantitative research with a descriptive correlational design, and it is a population research. The data collection technique uses the questionnaire and documentation methods. The research instruments used in this research are questionnaires and documentation guidelines. The data analysis uses the "kendal's tau" formula. The z formula is used for the significance test.The conclusions of the results of this study are:The teacher's teaching motivation at SMA Mardi Utomo Tarokan Kediri is generally high, with an average of 67.77.Students' learning achievement in Islamic Education at SMA Mardi Utomo Tarokan Kediri is generally good, with an average of 86.71.There is a strong influence between teacher's teaching motivation and students' learning achievement in Islamic Education at SMA Mardi Utomo Tarokan Kediri with a correlation coefficient of 0.986. The influence of teacher's teaching motivation on students' learning achievement in Islamic Education at SMA Mardi Utomo Tarokan Kediri is 54.96%.